2018
DOI: 10.1007/s00442-018-4219-y
|View full text |Cite
|
Sign up to set email alerts
|

Colors of night: climate–morphology relationships of geometrid moths along spatial gradients in southwestern China

Abstract: Color lightness of insects is an important ecological trait affecting their performance through multiple functions such as thermoregulation, UV protection and disease resistance. The geographical pattern of color lightness in diurnal insects are relatively well understood and largely driven by thermal melanism through the enhancement of insect activity. In nocturnal insects, however, the ecological function of color lightness in response to climatic factors is poorly understood, particularly at small spatial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 62 publications
6
19
1
Order By: Relevance
“…our results showed that the analyzed assemblages in warmer regions were consistently composed of, on average, lighter colored and smaller species of dragon-and damselflies compared to assemblages in cooler regions. Our continent-wide yet spatially explicit assessment of these relationships reconciles previous macroecological (Pinkert et al, 2017;Zeuss et al, 2014Zeuss et al, , 2017 and experimental (e.g., May, 1991;Samejima & Tsubaki, 2010;reviewed in Clusella-Trullas et al, 2007) Clusella-Trullas, Terblanche, Blackburn, & Chown, 2008;Heidrich et al, 2018;Schweiger & Beierkuhnlein, 2015;Stelbrink et al, 2019;Xing et al, 2018;Zeuss et al, 2014), confirm that thermal melanism is a mechanism of major importance in ectothermic organisms across regions and scales. Furthermore, consistent with the predictions of Bergmann's rule sensu lato, we found that the average body size of assemblages of odonates decreased with increasing temperature.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…our results showed that the analyzed assemblages in warmer regions were consistently composed of, on average, lighter colored and smaller species of dragon-and damselflies compared to assemblages in cooler regions. Our continent-wide yet spatially explicit assessment of these relationships reconciles previous macroecological (Pinkert et al, 2017;Zeuss et al, 2014Zeuss et al, , 2017 and experimental (e.g., May, 1991;Samejima & Tsubaki, 2010;reviewed in Clusella-Trullas et al, 2007) Clusella-Trullas, Terblanche, Blackburn, & Chown, 2008;Heidrich et al, 2018;Schweiger & Beierkuhnlein, 2015;Stelbrink et al, 2019;Xing et al, 2018;Zeuss et al, 2014), confirm that thermal melanism is a mechanism of major importance in ectothermic organisms across regions and scales. Furthermore, consistent with the predictions of Bergmann's rule sensu lato, we found that the average body size of assemblages of odonates decreased with increasing temperature.…”
Section: Discussionsupporting
confidence: 87%
“…Bergmann's rule, dispersal, freshwater insects, habitat-stability-dispersal hypothesis, local assemblages, macrophysiology, Odonata, thermal adaptation, thermal melanism hypothesis strong links between physiological trait and the environment, but these are often limited in spatial extent (Brehm, Zeuss, & Colwell, 2018;Dufour et al, 2018;Peters, Peisker, Steffan-Dewenter, & Hoiss, 2016;Xing et al, 2018). On the other hand, most of the studies conducted so far on the interspecific variation of color lightness and body size in ectothermic species over large geographical ranges are based on expert range maps generated by interpolating species occurrence records across suitable habitats (e.g., Pinkert, Brandl, & Zeuss, 2017;Zeuss, Brandl, Brändle, Rahbek, & Brunzel, 2014;Zeuss, Brunzel, & Brandl, 2017; but see Bishop et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While thermal constraints might well differentially govern activity patterns and habitat use of butterflies at sunny versus shaded sites (Pardonnet, Beck, Milberg & Bergman, 2013;Pryke, Vrdoljak, Grant & Samways, 2012), it is much less likely that this pertains to nocturnal insects to the same extent. A recent study based on color patterns of Geometridae moths in China indicated parallels to thermal environments along spatial gradients (Xing et al, 2018), yet another macro-ecological survey of Geometridae moths all across Europe indicated that non-thermal mechanisms could underlie these spatial patterns in F I G U R E 3 Venn diagrams indicating the species overlaps of moth assemblages of (a) total observed moths (b) Arctiinae, (c) Bombycoidea, and (d) Geometridae in relation to forest type: creek forest =creek, slope forest = slope, and ridge forest = ridge sites color lightness (Heidrich et al, 2018). However, the rather limited thermal gradients between the three forest habitat types can hardly explain the strong abundance and richness patterns that we found in strictly nocturnal moths.…”
Section: Moth Species Richness Abundance and Diversitymentioning
confidence: 99%
“…We took the mean 344 transmittance over specific ranges of wavelengths (UV, human-visible, and near-infrared) as the 345 dependent variable and we included latitude (absolute latitudinal distance to the equator), 346 nocturnality, wing length and their interaction as fixed factors. We included nocturnality as this 347 may play a role as suggested in opaque butterflies (Xing et al 2018) 348 For the latter two hypotheses, we had no specific expectation concerning the proportion 349 of UV transmittance; we thus did not test that variable. Table S3, 361 Figure S1).…”
mentioning
confidence: 99%